Performance analysis of solo Duck wave energy converter arrays under motion constraints. (15th November 2017) - Wu, Jinming; Yao, Yingxue; Zhou, Liang; Chen, Ni; Yu, Huifeng; Li, Wei; Göteman, Malin
Abstract: This paper studies the power capture performance of solo Duck wave energy converter (WEC) arrays. The barrier function method combined with a quasi-Newton BFGS optimization algorithm is applied to find the maximum captured power of the array when the Ducks are under motion constraints. Based on this optimized maximum captured power, the effects of separation distance, wave period, incident wave direction and Duck width on the array performance are investigated. For the two Ducks array, results show that the alternative constructive and destructive interaction stripes in the contour plot of the q -factor variation with non-dimensional separation distance are resulted from the diffracted wave pattern from each Duck, and the hydrodynamic interaction strength is reduced when constraints affect the performance. For the three Ducks array, the middle Duck shows larger variability of captured power than the side Ducks due to experiencing double in phase diffracted wave from the side ones. The captured power of the solo Duck WEC array is sensitive to incident wave direction, and arrays with Ducks of smaller width are found to have better performance in power capture efficiency. Abstract : Maximum captured power of solo Duck arrays is obtained under motion constraints. Domains of constructive and destructive interactions among Ducks are identified. Interaction strength is reduced when the excursions of Ducks are constrained. Captured power of solo Duck arrays is sensitive to incident wave direction. Arrays with Ducks of smaller width have better performance in efficiency.